2020
DOI: 10.3389/fped.2020.00405
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Birth Weight and Premature Birth With the Risk of Metabolic Syndrome: A Meta-Analysis

Abstract: The association of preterm or low birth weight (LBW) with the risk of metabolic syndrome is still unclear. This study aimed to assess the association between preterm or LBW and metabolic syndrome risk according to study or participants' characteristics. PubMed, Web of Science, and EMBASE were searched for epidemiologic studies on the association published up to April 30, 2020. Pooled odds ratio (ORs) and weighted mean differences (WMDs) with 95% confidence intervals (CIs) were calculated using the random-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…21 The reduction in birthweight is also strongly suspected to contribute to the development of obesity later in life. 22 Our study is also in line with some experimental studies reporting a decrease in body weight at birth in females and males prenatally exposed to stress, 23,24 though the animal model, route, GC dose and the duration of administration were different. Most of the studies in prenatal stress (GC administration or maternal stress during gestation) assessed only males or do not specify sex, although also demonstrating a reduction in body weight at birth.…”
Section: Discussionsupporting
confidence: 90%
“…21 The reduction in birthweight is also strongly suspected to contribute to the development of obesity later in life. 22 Our study is also in line with some experimental studies reporting a decrease in body weight at birth in females and males prenatally exposed to stress, 23,24 though the animal model, route, GC dose and the duration of administration were different. Most of the studies in prenatal stress (GC administration or maternal stress during gestation) assessed only males or do not specify sex, although also demonstrating a reduction in body weight at birth.…”
Section: Discussionsupporting
confidence: 90%
“…A growing body of evidence shows that prematurely born individuals have increased risks of individual chronic diseases (including metabolic syndrome [23,24], ischaemic heart disease [19], asthma [27] and depression [31]) in the early part of the life course. The findings presented here suggest that these risks also translate to increased risks of co-occurrence of multiple diseases among preterm born adolescents and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic disease multimorbidity was defined as one individual having records of two or more non-communicable chronic diseases (psychiatric or somatic) during the same or subsequent secondary care episode(s). The diseases constituting multimorbidity were selected based on evidence on commonly occurring diseases among preterm and term born adolescents and young adults [21,24,25,[36][37][38][39][40][41][42][43][44]. Multimorbidity was identified using data on both in-patient and out-patient hospital care (referred to in the Nordic context as specialised healthcare), based on diagnostic codes listed in S1…”
Section: Chronic Disease Multimorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm birth has been associated with an increased risk of developing cardiovascular disease and metabolic syndrome later in life (Liao et al, 2020). In fact, a meta-analysis of the literature has shown that preterm birth was significantly associated with increased fat mass, blood pressure, fasting glucose, and insulinemia, indicating that these individuals are at greater risk of developing cardiometabolic diseases during adulthood (Markopoulou et al, 2019).…”
Section: Pregnancymentioning
confidence: 99%